The efficiency of Paecilomyce farinosus as biocontrol to larve stage on second ad sixith instar larve of Trogoderma granarium (Everts) (Baghdad Science Journal, 2013)
The present study was conducted to determine the pathogenicity of Paecilomyces farinosus as biocontrol agents against Tragoderma granarium (khapra) under laboratory conditions with three concentrations ( 2.8 x 108 , 2.8 x 106 ,2.8 x104 spores/ ml). The laboratory results revealed that fungi showed it's higher pathogencity to larve stage on 2nd instar and 6th instar , although their capability differs according to the fungi concentrations this fungi caused higher mortality of 2nd larval instar 70% and 60% ,55% when it was used at concentrations 2 .8 x 106 ,2.8 x104 spores/ ml respectively. On the other hand on 6th larval instars 55% , 35% , 30% at concentrations ( 2.8 x 108 , 2.8 x 106 ,2.8 x104 spores/ ml) respectively, and the highest rate of distortions in the adult insects from the 2nd instar treatment than the adult insects from the 6th instar treatment concentration of this fungi.